Digital twin enabled smart microgrid system for complete automation: An overview - Buddhadeva Sahoo; Subhasis Panda; Pravat Kumar Rout; Mohit Bajaj; Vojtech Blazek (Results in Engineering)
Recent advancements in communication technology (CT) have ignited significant interest in the cutting-edge concept of the digital twin (DT), which holds the potential to revolutionize smart microgrid systems (SMGs). This study delves into the concepts and essential steps involved in constructing a DT-enabled smart microgrid (DT-SMG), emphasizing the necessity for complete automation to enhance device intelligence. Additionally, the paper discusses implementation standards for automation and the need for further modifications to accommodate future applications. The objective is to explore important DT-SMG use cases, and discuss the associated problems and potential solutions within DT-based automation frameworks. Recognizing the criticality of situational awareness, security, and resilience in DT-SMGs, the paper conducts a comparative study, highlighting the pros and cons gleaned from existing literature. These findings offer readers a comprehensive perspective, empowering them to develop and deploy DT technology across a spectrum of power system applications. Finally, the paper looks ahead to the future horizon of DT-SMGs.